Health and time allocated to market and household work in Turkey - DÜZGÜN ÖNCEL, BURCU (My University, 2022)
I examine the association between health and time allocation to market work and household work by using Turkish Time Use Survey in 2014. I define household work as the sum of time devoted to non-market work and leisure. In supplement to previous studies on the subject regarding Turkey, I consider two new aspects. One of these aspects I assess is the intertemporal component of time allocation decisions. The other aspect I cover is the potential selection bias of health status in time allocation decisions. For the former purpose, I focus on non-student, non-retired individuals. For the latter, I apply propensity score matching (PSM). Examining these two aspects, I find that as health improves, time devoted to market work significantly rises and time devoted to leisure falls for both males and females in this group. I also find that the association between health and time use on non-market activities is insignificant for males.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); health status; time use; propensity score matching; PSM; Turkey